Regulating impurities in pharmaceutical products: a tolerability of risk approach?. Issue 2 (March 2008) - Bouder, Frederic
This paper explores the implications of the EMEA guideline EMEA/CHMP/QWP/251344/2006 for pharmaceutical risk decisions. The guidelines propose to consider the intake of 1.5 µg/day of a genotoxic impurity as a 'threshold of toxicological concern'', and to treat this level as an acceptable risk (excess cancer risk of <10 -5 over a lifetime). The guidance document also introduces a specific decision-tree to assess the acceptability of genotoxic impurities. According to this decision-tree, when the presence of genotoxic impurities is unavoidable, their levels should be reduced 'as low as reasonably practicable'' (ALARP). In the UK, the Health and Safety Executive has developed a 'tolerability of risk'' (ToR) model to support ALARP requirements. The paper compares the EMEA risk-reduction requirements and the ToR model. EMEA/CHMP/QWP/251344/2006 introduces a risk-avoidance principle based on a controversial interpretation of 'pollution control''. The paper supports the view that this model is not optimal from a risk-management point of view. Using a ToR model could bring improvements to pharmaceutical risk decisions and would support a more practical and consensual approach to meeting the ALARP requirements.